Rival Queens: Actresses, Performance, and the Eighteenth-Century British Theater - Nussbaum, Felicity (University of Pennsylvania Press, Inc, 2010)
In eighteenth-century England, actresses were frequently dismissed as mere prostitutes trading on their sexual power rather than their talents. Yet they were, Felicity Nussbaum argues, central to the success of a newly commercial theater. Urban, recently moneyed, and thoroughly engaged with their audiences, celebrated actresses were among the first women to achieve social mobility, cultural authority, and financial independence. In fact, Nussbaum contends, the eighteenth century might well be called the "age of the actress" in the British theater, given women's influence on the dramatic repertory and, through it, on the definition of femininity. Treating individual star actresses who helped spark a cult of celebrity-especially Anne Oldfield, Susannah Cibber, Catherine Clive, Margaret Woffington, Frances Abington, and George Anne Bellamy-Rival Queensreveals the way these women animated issues of national identity, property, patronage, and fashion in the context of their dramatic performances. Actresses intentionally heightened their commercial appeal by catapulting the rivalries among themselves to center stage. They also boldly rivaled in importance the actor-managers who have long dominated eighteenth-century theater history and criticism. Felicity Nussbaum combines an emphasis on the celebrated actresses themselves with close analysis of their diverse roles in works by major playwrights, including George Farquhar, Nicholas Rowe, Colley Cibber, Arthur Murphy, David Garrick, Isaac Bickerstaff, and Richard Sheridan. Hers is a comprehensive and original argument about the importance of actresses as the first modern subjects, actively shaping their public identities to make themselves into celebrated properties.